2020
DOI: 10.1136/jitc-2020-000588
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-derived APCs are central to the response of PD1 checkpoint blockade and provide a therapeutic target for combination therapy

Abstract: BackgroundPD1 immune checkpoint blockade (αPD1 ICB) has shown unparalleled success in treating many types of cancer. However, response to treatment does not always lead to tumor rejection. While αPD1 ICB relies on cytotoxic CD8+ T cells, antigen-presenting cells (APCs) at the tumor site are also needed for costimulation of tumor-infiltrating lymphocytes (TILs). It is still unclear how these APCs develop and function before and during αPD1 ICB or how they are associated with tumor rejection.MethodsHere, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 68 publications
2
35
0
Order By: Relevance
“…Likewise, BATF3 deficiency also inactivates the responses to combined anti-PD-1 and anti-CD137 immunotherapy and the synergistic effect of poly I:C and FLT3LG ( 7 ). In addition to cDC1s, a recent study showed that moDCs, especially iNOS-producing Tip-DCs, are important in the response to PD-1 blockade ( 66 ).…”
Section: Immune-checkpoint Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, BATF3 deficiency also inactivates the responses to combined anti-PD-1 and anti-CD137 immunotherapy and the synergistic effect of poly I:C and FLT3LG ( 7 ). In addition to cDC1s, a recent study showed that moDCs, especially iNOS-producing Tip-DCs, are important in the response to PD-1 blockade ( 66 ).…”
Section: Immune-checkpoint Blockadementioning
confidence: 99%
“…Even though the presence of DCs is important for responsiveness to ICB, the functionality of DCs may improve the efficacy of this therapy. Anti-CD40 agonist antibody can promote DC differentiation and proliferation in the tumor microenvironment, resulting in systemic T-cell activation that produces a synergistic effect with ICB ( 66 - 68 ). In addition, engineered type I IFN targeting to DCs improves the functionality of DCs in antitumor immune responses and the efficacy of PD-L1 blockade ( 69 ).…”
Section: Immune-checkpoint Blockadementioning
confidence: 99%
“…Chow et al likewise presented that the cellular crosstalk mediated by cDC1s-derived CXCL9 and CXCR3 on T cells was pivotal for the proliferation and function of intratumoral CD8 + T cells in response to anti-PD-1 treatment. Apart from cDCs in tumor immunity, the scRNA-seq of human melanoma biopsies suggested that moDCs correlated with PD-1 responsiveness and effector T cell activity, and more importantly, targeting moDCs by anti-CD40 antibody could enhanced PD-1 ICB efficacy ( 138 ).…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 99%
“…These increases are different from what to expect from pembrolizumab monotherapy where activated CD8 T cell counts are increased only early on, at 2 or 4 weeks after start of treatment. 15 Failed T cell priming often needs repair through APC activation 16 before successful sensitization to PD-1/PD-L1 blockade and MHC II agonism with efti plays a critical role in generating T cell immunity by activating DCs [6][7][8] As efti or any other MHC class II agonist has not been tested yet in combination with an anti-PD-1 therapy, patients started efti injections in part A of the study at cycle 5 of pembrolizumab in order not to expose the subset of patients with pembrolizumab-induced immune-related AEs in the first 3 months of exposure to a second immunostimulant. Then, as no new safety signals were seen in part A, part B patients were treated with the combination from day 1 on.…”
Section: Discussionmentioning
confidence: 99%